A patent review of butyrylcholinesterase inhibitors and reactivators 2010–2017. (3rd June 2018) - Andrisano, Vincenza; Naldi, Marina; De Simone, Angela; Bartolini, Manuela
ABSTRACT: Introduction: Butyrylcholinesterase (BuChE) has obtained a renewed interest as therapeutic target in Alzheimer's disease (AD), when changes in BuChE activity and expression along disease progression were highlighted as well as correlation between BuChE levels and cognitive function. Areas covered: During the last eight years, fourteen patents on BuChE inhibitors (BuChEI) have been submitted. Only three of them relate to BuChE selective inhibitors, while four of them focus on multitarget inhibitors which address different key pathological factors other than BuChE. Two patents report on non-selective acetylcholinesterase (AChE)/BuChE inhibitors, while four patents deal with natural compounds and their derivatives. One patent relates to antitoxic agents to treat exposure to ChEI pesticides and nerve agents. Expert opinion: Increasing evidence supports BuChE as a more beneficial target in moderate-to-severe forms of AD in comparison to the well-known AChE. However, hitting a single pathological target is likely not sufficient to halt the disease progression. Therefore, patented BuChE inhibitors with a multifunctional profile may open new therapeutic avenues, since the additional activities could reinforce the therapeutic effects. Unfortunately, in vivo studies are limited and key parameters, such as ADMET data, are missing. This lack of information makes difficult to forecast the development of patented BuChEIs into effective drug candidates.